HIDDEN CURRICULUM - Edy Purwanto (ADIBA : JOURNAL OF EDUCATION, 2022)
Aspects that can affect the hidden curriculum, namely aspects that are relatively fixed and aspects that can change. What is meant by relatively fixed aspects are the ideologies, beliefs, and cultural values ​​of the community that affect schools, including determining what culture should and should not be passed on to the nation's generation. Meanwhile, aspects that can change include organizational variables, social systems and culture. Allan A Glatthom in his book Dede Rosyada also explains that these three variables are important in school management and development. The organizational variable is the teacher's policy in the learning process which includes how the teacher manages the class, how the lesson is given, how the grade promotion is carried out. The social system is the school atmosphere which is reflected in the patterns of relationships of all school components, which includes how the social patterns are between teachers and teachers, teachers and students, teachers and school staff, and so on. Cultural variables are social dimensions related to belief systems, values, and cognitive structures.